Participatory Mapping for RT, Dusun, and Village Boundary Delimitation in Dlingo, Bantul, Indonesia - Syahlianawati, Ulfah; Sutanta, Heri (Jambura Geoscience Review, 2026)
Village, hamlet, and neighbourhood boundary delineation is essential for effective governance, spatial planning, and population administration, yet many rural areas in Indonesia still lack formally recognized boundary maps. This study aims to establish accurate administrative boundaries in Dlingo Village, Bantul Regency, through a participatory mapping approach that integrates field surveys, high-resolution satellite imagery, cartometric interpretation, and GIS-based analysis. Field data were collected using handheld GPS devices and subsequently plotted and digitized to construct preliminary boundary lines. The mapping process was refined through Focus Group Discussions involving village officials, hamlet heads, and neighbourhood leaders, ensuring that spatial interpretations aligned with local knowledge and long-standing territorial agreements. The results show that most village boundaries follow natural landscape features, particularly rivers, which assisted cartometric delineation, although terrain conditions posed challenges during field verification. A comparison between field-surveyed boundaries and OpenStreetMap data revealed significant positional discrepancies, confirming the need for ground-truthing in rural boundary mapping. The final administrative boundary maps reflect both technical accuracy and community consensus, providing a reliable reference for governance, development planning, and the establishment of a village information system. This study demonstrates the effectiveness of combining participatory approaches with geospatial techniques and offers a practical model for addressing boundary ambiguities in other rural regions.